2022
DOI: 10.1111/jonm.13894
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence based prediction models for individuals at risk of multiple diabetic complications: A systematic review of the literature

Abstract: Aim: The aim of this review is to examine the effectiveness of artificial intelligence in predicting multimorbid diabetes-related complications.Background: In diabetic patients, several complications are often present, which have a significant impact on the quality of life; therefore, it is crucial to predict the level of risk for diabetes and its complications.Evaluation: International databases PubMed, CINAHL, MEDLINE and Scopus were searched using the terms artificial intelligence, diabetes mellitus and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Prior studies have shown to improve model performance with inclusion of numerical features such labs and vitals (body mass index, blood pressure, lipid profiles, etc.) 15,55,56 . BERT inherently processes inputs as tokens, including numerical features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown to improve model performance with inclusion of numerical features such labs and vitals (body mass index, blood pressure, lipid profiles, etc.) 15,55,56 . BERT inherently processes inputs as tokens, including numerical features.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the prior research was focused on predicting risk scores using a limited number of risk factors, often curated from previous literature [8][9][10][11][12][13][14] . Despite many machine learning (ML) and deep learning (DL) models that emerged in recent research, classical ML models dominated these studies-mostly limited to performance comparisons, with only a minority delving into exploring novel risk factors and discovering new knowledge 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…AI technology indeed helps health care professionals, provides more care for a larger number of patients, makes better clinical decisions, and reduces unnecessary hospitalization and health care costs [18] . Gosak et al [19] investigate the effectiveness of AI within predicting complications associated with multimorbid diabetes mellitus through bibliometric studies. Mihevc et al [20] find that AI can be integrated into the platform to optimize the cost structure of remote monitoring of AH and T2D older adults in primary care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Graili et al [24] systematically discuss AI in outcomes research, cover the scope of AI techniques used in outcomes research to expend the knowledge of decision-makers. Gosak et al [19] investigate the effectiveness of AI in predicting complications caused by multimorbid diabetes-related using bibliometrics. Few studies systematically and scientometrically review the overall picture of medical AI.…”
Section: Literature Reviewmentioning
confidence: 99%